Gender-Wage Gap in the Korean Air Transport Industry: Evidence From Microdata Between the Years 2015 and 2022 - Zeljana Zmire; Hye-Jeong Lee; Yolanda T. Montances; Sohee Yang; Seul Ki Lee (SAGE Open, 2025)
Gender-based disparities in air transport industry have been reported in the literature, while less attention has been given to the gender-wage gap. Meanwhile, Korea constitutes a unique environment for gender-wage disparity. Suspecting the gender-wage gap in the air transport industry of Korea, this study utilizes microdata made available by the Ministry of Employment and Labor between the years 2015 and 2022. Through empirical analysis of data, the current study finds that male workers earn 6.3% more than the female workers working in the industry. Age did not have a significant interactive effect with gender when determining wage, but education had a significant interaction effect with gender on wage determination. In overall, results show support for demand-side explanations rather than supply-side explanations of the gender-wage gap. Theoretical considerations and implications for the practitioners are discussed along with the findings of the study.